Social Policy Expansion from Below? the Case of Chile S Student Movement and Free Tuition Higher Education - Disi-Pavlic, R (Elsevier Ltd, 2023)
Scholars have long sought to establish the strategies through which social movements can impact policy adoption. Yet, there is little evidence on the role they may play in policy expansion. We study the role of social movements in broadening the scope of social policies by analyzing whether Chile s student movement impacted the expansion of the free college tuition policy between 2015 and 2020. We evaluate three mechanisms to assess the student movement s influence on free tuition expansion. First, movements may use protests to affect the expansion process through disruption. Second, they can make use of their connections with and presence in parties and the bureaucracy to channel their demands and influence decision-making instances. Finally, movements may also try to shape public opinion to affect the scope of the policy through mobilizations and other forms of influence. We use a process tracing design to examine these mechanisms. We collect and analyze evidence from 32 elite interviews, congressional and administrative records, web scraped news, and public opinion and protest event data. Our results show that students influenced the implementation and expansion of the free tuition policy through all mechanisms using different strategies. First, students used protests to set free tuition in the public agenda. Second, and the most important strategy, by means of connections with incumbent parties and the presence of former student activists in the Education Ministry and in Congress, they indirectly influenced policy expansion. Finally, and indirectly, they shaped public opinion in favor of free tuition. Students played a role in defining the pace and scope of the policy but could not imprint all their demands. Overall, our analysis sheds light over the ways in which social movement can influence the implementation of policies, thus, expanding the scope of equity-enhancing social policies in Latin America and beyond. © 2023 Elsevier Ltd